Let Burn : The Making and Breaking of a Firefighter/Paramedic - Wentz, Rachel K. (Book collections on Project MUSE.)
In 1985, desiring a meaningful, high-paced career in public service, Rachel Wentz left her university studies to become a firefighter/paramedic. Only the eighth woman hired by the Orlando Fire Department, a highly competitive department steeped in tradition, Wentz excelled, completing an AS in Fire Science, a master's in public administration, and numerous specialized training courses to prepare her for an administrative position within the department. Wentz spent eleven years with OFD, experiencing a career that was every bit as exciting and challenging as she had sought. A moving, candid, a.